Optoelectronic characteristics of single InP nanowire grown from solid source. (14th April 2015) - Kamimura, H; Dalmaschio, C J; Carrocine, S C; Rodrigues, A D; Gouveia, R C; Leite, E R; Chiquito, A J
Abstract: InP nanowires were synthesized on quartz substrates via vapour phase deposition using gold seeds and solid source. The properties of the InP nanowires were investigated by x-ray diffraction, scanning electronic microscopy (FEG-SEM) and high resolution transmission electron microscopy demonstrating micrometric lengths and diameter distribution ranging from 40 to 100 nm with crystalline core. Photo-current on-off characteristics were obtained from single nanowire devices, presenting a delay of a few seconds in the current decay when the illumination is turned off. This time is much larger than some usual microseconds decays and may be caused by localized states whose presence was confirmed by thermally stimulated current TSC measurements.